(untitled) (Semiárida, 2020)
Species of phytophagous nematodes that damage tomato crops in Colonia 25 de Mayo (La Pampa) Argentina are studied. The techniques used for- sampling, and nematodo separation are shown. The Genera Melidogyne, Trichodorus and Hemicycliophora are mentioned for the first time in this region.